MALDI-TOF MS Applications to the Detection of Antifungal Resistance: State of the Art and Future Perspectives - Florio, Walter; Tavanti, Arianna; Ghelardi, Emilia; Lupetti, Antonella (Frontiers in Microbiology, 2018)
MALDI-TOF MS technology has made possible revolutionary advances in the diagnosis of infectious diseases. Besides allowing rapid and reliable identification of bacteria and fungi, this technology has been recently applied to the detection of antimicrobial resistance determinants. Assessment of β-lactamase activity by visualizing the hydrolysis of the β-lactam ring, detection of genes or peptides conferring antibiotic resistance, identification of biomarkers correlated with drug resistance/non-susceptibility, and the comparison of proteomic profiles of bacteria/yeast incubated with or without antimicrobial drugs are among the most widely studied methods. Increasingly effective and accurate MS tools and instruments as well as the possibility to optimize analytical parameter settings for targeted applications have generated an expanding area in clinical microbiology diagnostics. Antimicrobial resistance to a number of antibiotics belonging to different classes has been successfully tested, opening this field to further clinically important developments. Special applications of MALDI-TOF MS to early detection of drug resistant microorganisms in patients with bloodstream infections are being evaluated; this would allow a considerable time saving in streamlining the antibiotic therapy for a better outcome of critically ill patients. In the present study, the state of the art of MALDI-TOF MS applications to antimicrobial resistance/non-susceptibility assessment is reviewed, and cutting-edge developments are discussed.